Analisis darah (hemoglobin, hematokrit, dan trombosit) pada pasien anak demam berdarah dengue - Agni Yudhaswara, Novian; Djuma, Agustina Wilhelmina; Nurdin, Tri Wulandari (JURNAL KESEHATAN PRIMER, 2023)
Introduction: Dengue Hemorrhagic Fever (DHF) is an infection caused by the Dengue virus which is transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. Based on laboratory criteria, low platelet count (thrombocytopenia) and plasma leakage are important indicators for DHF. The purpose of this study was to analyze Hb levels, Ht levels, and platelet counts and their relationship in DHF patients so that when these values are at the threshold, health workers can anticipate and provide ideal care. Methods: This article is a descriptive retrospective study by taking secondary data at RSUD S.K. Lerik City of Kupang in 2020 with a total sample population of 135 DHF pediatric patients (0-11 years). Results: The results of this study, Hb values were below normal at 10.8 ± 1.4 g/dL in 52 (39%) patients, Ht values were above normal at 42.5 ± 2.3% in 81 (60%) patients, and platelet values were not normal or low 110,000 ± 12,500 per microliter of blood in 130 (97%). Researchers also wanted to show the relationship between Hb, Ht, and Platelets in the analysis with the Pearson Correlation Test (α = 0.05). Conclusion: The conclusion of this article is that there is no correlation between Hb and Ht and platelets, while Ht and platelets have a significantly low correlation (r=-0.32), which means that there is a relationship between high hematocrit and low platelet values in pediatric DHF patients so that patients DHF in children needs to be examined both.